Rural Women and Non-Farm Employment - Result of a Field Study in Irengbam Village of Manipur (International Journal of Food and Nutritional Sciences, 2022)
The paper attempts to examine the economic contribution of rural women in Manipur through their earnings from various activities in the non-farm sector. The paper shows that non-farm sector employment plays a significant role in supporting the livelihoods of rural families in the state of Manipur. The paper is based on a field survey in Irengbam village of Bishnupur district in Manipur.